Surgical stimulation of uveoscleral outflow is an alternative to cyclodestructive procedures - E.A. Korchuganova; A.Yu. Kazantzeva (РМЖ "Клиническая офтальмология")
E.A. Korchuganova, A.Yu. Kazantzeva Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to assess clinical efficacy and safety of surgical scleral rejection (SSR) vs. transscleral diode laser cyclophotocoagulation (TSCPC) in primary open-angle glaucoma (POAG) and secondary glaucoma (SG). Patients and Methods: study (prospective) group included 84 patients with POAG and SG after SSR. Control (retrospective) group included 80 patients after TSCPC. In addition, the patients were distributed by age and the stage and type of glaucoma, i.e., 128 patients were diagnosed with POAG and 36 patients were diagnosed with secondary thrombotic glaucoma. Follow-up was 24 to 36 months. IOP measurements, tonography (to assess the coefficient outflow facility / COF), ultrasound biomicroscopy of the anterior segment, visual acuity measurement, and visual field testing were performed. Results: no complications after SSR were reported in patients with POAG and SG. In contrast, postoperative complications (choroidal effusion, hyphema, and uveitis) were reported in 14% of patients after TSCPC. Long-term IOP-lowering efficacy of both procedures was similar (87% after SSR and 89% after TSCPC). In POAG, greater IOP reduction was seen after TSCPC (by 39.11%) compared to SSR (by 31.58%) (p<0.05). Meanwhile, in patients with SG, treatment outcomes were similar (IOP reduced by 36.78% after TSCPC and by 35.26% after SSR). In long-term follow-up, PVF reduced by 10.76% vs. baseline after TSCPC but increased by 11.19% vs. baseline after SSR (p≤0.05). Surgery resulted in the improvement or stabilization of visual functions. Ultrasonography has demonstrated that outflow pathways (intrascleral space and filtering bleb) remain functional after SSR in long-term fol low-up. Conclusion: SSR is an alternative to cyclodestructive procedures in POAG and SG. Sclera being the final point of the uveoscleral outflow is a perspective entity to develop surgical approaches to glaucoma treatment. Keywords: surgical scleral resection, uveoscleral outflow, sclera, primary open-angle glaucoma, secondary glaucoma, glaucoma surgery, transscleral diode laser cyclophotocoagulation. For citation: Korchuganova E.A., Kazantzeva A.Yu. Surgical stimulation of uveoscleral outflow is an alternative to cyclodestructive procedures. Russian Journal of Clinical Ophthalmology. 2021;21(1):9–13. DOI: 10.32364/2311-7729-2021-21-1-9-13.